Peningkatan Kemampuan Guru dalam Mendukung Penerapan Implementasi Kurikulum Merdeka di SMP Negeri 1 Montasik - Nazariana, Nazariana; Akmaluddin, Akmaluddin; Kasmini, Lili (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to evaluate the implementation of the independent learning curriculum at SMP Negeri 1 Montasik, including the stages of input, process, and output. This research uses qualitative descriptive research methods with research instruments in the form of interviews, observations, and documentation. This research was conducted at SMP Negeri 1 Montasik. Data analysis is carried out qualitatively with stages of data reduction, data presentation, and conclusion drawing. Based on the research results, respondents expressed positive expectations for the Independent Curriculum, emphasizing the desire for consistent implementation to reduce the administrative burden on teachers. The hope also includes improving student character, creativity, and achievement, as well as the importance of regular training for teachers. Observations show that the school has succeeded in developing key competencies through understanding, implementing, and assessing the Independent Curriculum. Curriculum-based learning plans provide effective guidance, while the use of learning methods and technology integration increases student engagement. Teachers demonstrate the ability to assess learning outcomes according to the Independent Curriculum, with reflection and improvement activities. Training and collaboration between teachers create a creative environment. Even though there were obstacles, teachers managed to overcome them with effective strategies, and the Merdeka Curriculum succeeded in inspiring students to learn independently and critically